2014
DOI: 10.9734/ejmp/2014/8549
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Biological Potential of Cassia tora Linn.

Abstract: Cassia tora Linn. (Caesalpinaceae) is a semi-wild annual herb grown widely in different places of south-east Asia including India, Northern Australia and Americas. This plant species is well known for having potential in traditional medicine practices for the treatment of a variety of disorders and ailments ranging from simple cough, hypertension to diabetes. Recent scientific investigation reveals its phytochemical as well as biological potential. C. tora has been proven to be medicinally effective for having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…According to the literature survey, secondary metabolites isolated from different extracts of Cassia tora have been reported to have therapeutic importance. 24 For example; anthraquinones from the seeds of Cassia tora is reported to show inhibitory activity on protein glycation and aldose reductase and antimicrobial activity 25 .…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature survey, secondary metabolites isolated from different extracts of Cassia tora have been reported to have therapeutic importance. 24 For example; anthraquinones from the seeds of Cassia tora is reported to show inhibitory activity on protein glycation and aldose reductase and antimicrobial activity 25 .…”
Section: Resultsmentioning
confidence: 99%
“…The leaves were used in traditional systems of medicine for eye ailments and are a good source of antioxidant secondary metabolites. Studies have reported the presence of many polyphenolic compounds such as anthraquinones, anthocyanocides, flavonoids, sterols and terpenoids in the leaves of cassia tora (Sarwa et al, 2014) and HPLC analysis of cassia tora leaves (Supplementary data) indicated the presence of chrysophanol, the marker compound of the plant. Studies have shown that chrysophanol has free radical scavenging properties and reduced the oxidative stress in experimental animals (Rani et al, 2010) and no reports are available on the anticataractogenic effect of chrysophanol till to date.…”
Section: Discussionmentioning
confidence: 96%
“…The seed of charota resembles a coffee seed, therefore also known as wild coffee in India. Some other vernacular name is Foetida cassia, Ktanta, and chakaramarda in Indian languages [3]. Cassia tora regarded as safe for human consumption and used in the food industry for many years.…”
Section: Introductionmentioning
confidence: 99%